Between distress and educational well-being. Life stories of the second generations - Francesca Dello Preite (University of Bologna, 2020)
In recent decades, second generation foreign pupils have become a mainly significant component within the different social contexts of our country. Awareness about this new phenomenon is taking place thanks to an increasingly large number of interdisciplinary research which aims to analyze how these young people live their daily experiences and how the local Educational bodies, including the school, facilitate their inclusion. This contribution aims to address these issues by referring to the results of a qualitative research conducted at some secondary schools in Tuscany in which 120 second generation teenagers participated. In particular, this article focuses on the life stories of a subgroup of the girls interviewed, to demonstrate that, in addition to the many cases of school and/or social discomfort, these girls are living more and more experiences marked by success and educational well-being to which they - and their families - attach high value to both their present and their future.